The Changes of Nutrient Content of Cassava Peel (Manihot esculenta Crantz) That Fermented by Indigenous Microorganisms (IMO) As Animal Feed - Indra Satria Siburian; Edhy Mirwandhono; Yunilas; Tri Hesty Wahyuni; Hamdan (Jurnal Peternakan Integratif, 2019)
Cassava peel was the waste of processing cassava which is promising enough to be used as alternative animal feed. However, cassava peel has a fairly low nutrient content. Fermentation was one of the way to increase the quality of cassava peel. Fermentation used in this research utilized Indigenous Microorganisms (IMO) with the main substance was the cassava peel itself. This research lasted for 3 months started from December 2018 to February 2019 at the Laboratory of Microbiology and Laboratory of Feed Processing Science and Technology Department of Animal Science Faculty of Agriculture University of Sumatera Utara and Laboratory of Agrichemists and Natural Resources at the Industrial Research and Standardization Office of Medan. This research was designed using Completely Randomized Design (CRD) factorial pattern of 3 x 3 with 3 replications, as factor I was the dose of Indigenous Microorganisms (IMO) and factor II was the duration of fermentation. The parameters measured were water content/dry matter, crude fat, crude protein, crude fibre, ash, and Non Nitrogen Free Extract (NNFE) using proximate analysis. The results showed that fermentation of cassava peel using Indigenous Microorganisms (IMO) with the variation of Indigenous Microorganisms (IMO) dose and duration of fermentation give effects, that were increased water content, crude protein, and Non Nitrogen Free Extract (NNFE) and decreased dry ingredient, crude fat, crude fibre, and ash content.